A Speech-Centric Perspective for Human-Computer Interface - A Case Study - Deng, Li; Yu, Dong (Journal of VLSI Signal Processing Systems (Special Issue on Multimedia Signal Processing), 2005)
Speech technology has been playing a central role in enhancing human-machine interactions, especially for small devices for which graphical user interface has obvious limitations. The speech-centric perspective for human-computer interface advanced in this paper derives from the view that speech is the only natural and expressive modality to enable people to access information from and to interact with any device. In this paper, we describe some recent work conducted at Microsoft Research, aimed at the development of enabling technologies for speech-centric multimodal human-computer interaction. In particular, we present a case study of a prototype system, called MapPointS, which is a speech-centric multimodal map-query application for North America. This prototype navigation system provides rich functionalities that allow users to obtain map-related information through speech, text, and pointing devices. Users can verbally query for state maps, city maps, directions, places, nearby businesses and other useful information within North America. They can also verbally control applications such as changing the map size and panning the map moving interactively through speech. In the current system, the results of the queries are presented back to users through graphical user interface. An overview and major components of the MapPointS system will be presented in detail first. This will be followed by software design engineering principles and considerations adopted in developing the MapPointS system, and by a description of some key robust speech processing technologies underlying general speech-centric human-computer interaction systems.